2012
DOI: 10.2147/ndt.s32767
|View full text |Cite
|
Sign up to set email alerts
|

Acute neuropsychiatric disorders in adolescents and young adults with Down syndrome: Japanese case reports

Abstract: Background:The aim of this study was to evaluate acute neuropsychiatric disorders in adolescents and young adults with Down syndrome. We report 13 Japanese adolescents or young adults with Down syndrome who developed acute neuropsychiatric disorders including withdrawal, depression, obsessive-compulsive behaviors, and occasional delusions or hallucinations.Methods:The following information was collected from each patient: age at onset of acute neuropsychiatric disorder, complications, signs and symptoms, perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…Recently, Akahoshi et al in Japan, reported 13 DS individuals with good premorbid function who developed acute neuropsychiatric symptoms as adolescents or young adults. 5 Their symptoms, including psychomotor slowness in 100% and stupor or catatonia in 15%, strongly suggest catatonia syndrome. Their official diagnoses were major depressive (54%), obsessive, psychotic NOS, anxiety, and adjustment disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Akahoshi et al in Japan, reported 13 DS individuals with good premorbid function who developed acute neuropsychiatric symptoms as adolescents or young adults. 5 Their symptoms, including psychomotor slowness in 100% and stupor or catatonia in 15%, strongly suggest catatonia syndrome. Their official diagnoses were major depressive (54%), obsessive, psychotic NOS, anxiety, and adjustment disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Some are referring to this condition as "Down Syndrome Disintegrative Disorder," [Prasher, 2002;Devenny and Matthews, 2011;Worley et al, 2014] "Newonset Autistic Regression," [Worley et al, 2014] "Catatonic Psychosis," [Rollin, 1946] "Acute Regression of DS," [Akahoshi et al, 2012] or "Catatonia in DS" [Ghaziuddin et al, 2015]. This sudden process often involves loss of daily living skills, cognitive decline, psychomotor slowing, disordered sleep, loss of speech, unintentional weight loss, uncharacteristic anxiety, depression and/or mood lability, and new-onset or worsening repetitive thoughts and behaviors [Prasher, 2002;Devenny and Matthews, 2011;Worley et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…He hypothesized that this regression could be a process closely related to the defects of serotonergic and cholinergic systems. The effect of SSRI on acute regression in young adults with DS was also reported (case 2 in the study of Akahoshi et al) [16]. Neurotransmitters play a critical role in brain development and mood regulation.…”
Section: Discussionmentioning
confidence: 74%